1991
DOI: 10.1203/00006450-199111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Mild Oligonephronia Induced In Utero by Gentamicin in the Rat

Abstract: ABSTRACT. Renal clearance studies and morphologic observations were performed in rats aged 14, 21, and 28 d and 3, 6, 9, and 12 mo born with a 20% reduction in nephron number after administration of 75 mg/kg/d of gentamicin to their mothers during the second half of gestation. Gentamicin was still present in urine 3 mo after birth. Morphologic damage characteristic of gentamicin accumulation was observed in the kidney on d 14 and 21. Adequate compensatory adaptation to oligonephronia occurred for glomerular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…Similar alterations are found in the offspring of pregnant rats treated with an aminoglycoside (16). Such offspring have also been shown to have a lower nephron number and develop subsequent glomerulosclerosis with aging (17)(18)(19). In line with these findings, it has been shown that organ culture of early metanephroi in media supplemented with gentamicin also leads to impaired nephron formation (20).…”
Section: Nephrotoxic Drugssupporting
confidence: 72%
“…Similar alterations are found in the offspring of pregnant rats treated with an aminoglycoside (16). Such offspring have also been shown to have a lower nephron number and develop subsequent glomerulosclerosis with aging (17)(18)(19). In line with these findings, it has been shown that organ culture of early metanephroi in media supplemented with gentamicin also leads to impaired nephron formation (20).…”
Section: Nephrotoxic Drugssupporting
confidence: 72%
“…However, we cannot exclude the possibility that pathological changes might occur over a longer time or if the reduction in glomerular number were more marked, as in uninephrectomy. In a rat model of oligonephronia induced in utero by gentamicin and using descriptive histological techniques only, mesangial lesions and glomerular sclerosis were more common than in control animals at 24 months [31]. A parallel may be drawn with renal transplant donors, where longitudinal studies have shown no adverse effects in the early years after nephrectomy [32] but an increased prevalence of microalbuminuria and hypertension after 12-31 years [33].…”
Section: Discussionmentioning
confidence: 96%
“…Given that it is well known the bigger incidence in black race and close resemblance to HIV-associated nephropathy, a search for possible viral etiology and socioeconomic influences appears justified. Merlet-Bénichou et al has found reduced numbers of glomeruli and larger glomerular volumes in newborn rats exposed to toxins in utero and in infants born with small placentas and low birth weights; these observations suggest that socioeconomic differences, such as poor nutrition or exposure to toxins during gestation, might affect the developing kidney and result in a reduced glomerular population with larger glomerular volume (6,13) .…”
Section: Discussion Of Resultsmentioning
confidence: 99%